Safe harbors - Hano, Renee Roth (New York: Four Winds Press, 1993)
Having survived the Nazi occupation of France, teenage Renee goes to live and work in New York and, while there, begins to come to terms with his Jewish identity and her war experiences.
English
Keywords: Juvenile fiction